Outcome off Primary Coronary Angioplasty by Radial Route: Study on 100 Cases - Ratnani, Dr. Dilip; Ratnani, Dr. Rekha (International Journal of Innovative Research in Medical Science, 2018)
Recently radial artery is being used as a vascular access route for coronary procedures. Primary angioplasty with transfemoral procedure is associated with high access site bleeding complications due to use of potent antiplatelets and anticoagulants therefore radial access should be preferred if the operators are experienced and familiar with the technique. Methods: Total 100 pa‡…tients were included in the study in which procedure was performed by the trans radial route. All routine laboratory investigations were performed. Support of a temporary pacemaker was kept ready. All patients were prepared according to the Cardiac Catheterization Laboratory Standards. Radial artery cannulation was performed. Results: 100 patients were included in the study selected for radial route. Mean age of the patients who underwent primary CAI was 59±8.4. The most affected artery in the as shown angiography was Left anterior descending (58%) followed by Right coronary artery (41%). Least affected artery was left main (6%) and Ramus intermedius (6%). Mean of diseased vessels was 1.34 ± 1.25. Crossover from radial to femoral route was done on 5 patients of which 2 patients were having radial artery anomaly and in 3 patients arterial puncture was not successful. Mean hospital stay of the patients after procedure was 6.8 ± 2.1. Conclusion: transradial approach for coronary procedures is a safe technique and gives similar clinical results to transfemoral access. Complications at the radial access site are negligible. Length of hospital stay, time to mobilisation and cost all are reduced in the transfemoral approach.